The Effect Of CAR, NPL, NIM, And LDR On Financial Performance On Banking Companies Listed In IDX - Mutiara Putri (Universitas Islam Lamongan, 2022)
This study aims to determine the effect of CAR, NPL, NIM, and LDR on financial performance with ROA as a measuring tool. This research was conducted on banking companies listed on the Indonesia Stock Exchange for the period 2018-2020. The research method used is quantitative research with an associative approach. The sample in this study were 21 banking companies. The data analysis used is multiple linear analysis. Based on the results of data analysis, it shows that the CAR and LDR has no significant effect on ROA. NPL has a significant and negative effect on ROA. NIM has a significant effect on ROA.